The mediating role of attitude and environmental awareness in the influence of green advertising and eco-labels on green purchasing behaviors. - Carrión-Bósquez, N. (2025)
Purpose This study aims to identify whether green advertising and eco-labels influence the purchasing behaviors of organic products or whether the influence of such behaviors is presented through the mediating effect of the attitude and environmental awareness of millennials. Design/methodology/approach This study used a quantitative, correlational and cross-sectional design. A total of 430 millennials participated in the study. The questionnaire consisted of 20 questions, distributed across five variables. It was applied to people outside shopping centers in the city of Quito and Guayaquil, Ecuador. The results were subjected to statistical tests to determine the internal consistency of the instrument. The convergent and discriminant validity of the research model was verified through confirmatory factor analysis and structural equation modeling. SPSS 20 and AMOS 24 were used for statistical analyses. Findings The study identified that attitude and environmental awareness mediate the relationship between green advertising and green purchasing behaviors, as well as the relationship between eco-labels and green purchasing behaviors. Furthermore, it has been proven that green advertising directly influences the green purchasing behaviors of organic products among millennials, whereas eco-labels do not. Originality/value This study is among the initial investigations to delineate the connection between elements of green marketing and the buying patterns of organic goods among millennials in an emerging economy. The study provides answers to earlier scholarly inquiries that proposed examining the correlation among the constituents of the theorized framework.